2015
DOI: 10.1080/1091367x.2015.1038822
|View full text |Cite
|
Sign up to set email alerts
|

Factorial Validity and Reliability of the Curricular Goals in Physical Education Questionnaire

Abstract: This study aimed to examine the validity and reliability of an instrument designed to measure student perceptions of curricular goals in physical education, the Curricular Goals in Physical Education Questionnaire. Participants were 879 Finnish students from grades 7 to 9 (412 girls, 467 boys; mean age 13.81). An exploratory factor analysis was performed on Sample 1 (n = 287), revealing a four-factor solution and suggesting that factor structure be cross-validated with confirmatory factor analysis in Sample 2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 45 publications
0
3
1
Order By: Relevance
“…The current findings on gender are different from previous studies, demonstrating that boys have higher PL or physical activity than girls [30]. Although it is generally suggested that physical activity and PL decreases with increasing in age [38,39], there was no difference between gender in the current study. This is contrary to the results of a study in which male students generally have more physical activity than female students [40].…”
Section: Discussioncontrasting
confidence: 99%
“…The current findings on gender are different from previous studies, demonstrating that boys have higher PL or physical activity than girls [30]. Although it is generally suggested that physical activity and PL decreases with increasing in age [38,39], there was no difference between gender in the current study. This is contrary to the results of a study in which male students generally have more physical activity than female students [40].…”
Section: Discussioncontrasting
confidence: 99%
“…Another important issue is that PE teachers in Greece should consider using a positive youth development perspective (Côté and Fraser-Thomas, 2016) during the design of learning activities. This is important when it comes to gender, considering the fact that boys and girls may differently perceive the importance of PE curriculum goals (Lyyra et al, 2015). Nonetheless, it appears that teachers in Greece need to be more cognizant of potential "gender biases" in PE expectations, so that they can shape the pedagogical delivery of their lessons accordingly.…”
Section: Discussionmentioning
confidence: 99%
“…The authenticity of the subject matter/selected content is also related to ensuring that the topics are not obsolete. Therefore, a check and balance system on the curriculum content and flexibility of replacement/modification is also needed [60]. Second, the selection criterion aids learners in attaining self-reliance economically by giving them a chance to experience observing and performing the field study.…”
Section: The Standards For Selecting the Contents Of Curriculamentioning
confidence: 99%